Long-term success of oral health intervention among care-dependent institutionalized seniors: findings from a controlled clinical trial - Schwindling, Franz Sebastian; Krisam, Johannes; Hassel, Alexander J.; Rammelsberg, Peter; Zenthöfer, Andreas (Community dentistry and oral epidemiology, 2018)
Objectives: The purpose of this work was to investigate the long-term effectiveness of oral health education of caregivers in nursing homes with care-dependent and cognitively impaired residents. Methods Fourteen nursing homes with a total of 269 residents were allocated to a control group, with continued normal care, or to an intervention group. Allocation was performed at nursing home level. In the intervention group, caregivers were given oral health education, and ultrasonic cleaning devices were provided to clean removable prostheses. Oral health was assessed at baseline and after 6 and 12 months by use of the Plaque Control Record (PCR), Gingival Bleeding Index (GBI), Community Periodontal Index of Treatment Needs (CPITN) and Denture Hygiene Index (DHI). Mixed models for repeated measures were performed for each target variable, with possible confounding factors (intervention/control group, age, sex, residence location and care-dependence). Results In the control group, no changes of target variables were observed between baseline and the 6- and 12-month follow-ups. After 6 and 12 months, PCR and DHI were significantly improved in the intervention group. For PCR, the intergroup difference of improvements was −14.4 (95% CI: −21.8; −6.9) after 6 months. After 12 months, the difference was −16.2 (95% CI: −27.7; −4.7). For DHI, the intergroup difference compared to baseline was −15 (95% CI: −23.6; −6.5) after 6 months and −13.3 (95% CI: −24.9; −1.8) after 12 months. There was neither a statistically significant effect on GBI nor on CPITN. Care-dependency showed a substantial trend to smaller improvements in PCR (P = .074), while an inverse effect was apparent for DHI (P < .001). Conclusions Education of caregivers improves and maintains the oral health of care-dependent nursing home residents over longer periods. Use of ultrasonic devices is a promising means of improving denture hygiene among the severely care-dependent. Such interventions can be easily and cheaply implemented in routine daily care.
Version of record online: 20 September 2017
Gesehen am 19.06.2018